Anterior Communicating Artery Aneurysms: Anatomical Considerations and Microsurgical Strategies - Chen, Junhui; Li, Mingchang; Zhu, Xun; Chen, Yan; Zhang, Chunlei; Shi, Wenwen; Chen, Qianxue; Wang, Yuhai (Frontiers in Neurology, 2020)
Anterior communicating artery aneurysms account for 23-40% of ruptured intracranial aneurysms and 12-15% of unruptured aneurysms and are the most common intracranial ruptured or unruptured aneurysms. Because they have relatively complex anatomical structures and anatomical variations and are adjacent to important blood vessels and structures, in the process of microsurgical exposure of an Anterior communicating artery aneurysm, attention should be paid not only to the anatomical characteristics of the aneurysm itself but also to the adjacent important blood vessels and perforating arteries; therefore, both surgical clipping and endovascular embolization are serious challenges for neurosurgeons. No matter which treatment is chosen, it is necessary to determine the structure of the Anterior communicating artery and its perforating arteries as well as whether there is fenestration deformity of the Anterior communicating artery and the relationship between bilateral A1-A2 before surgery. The shape and size of the aneurysm itself and its location relative to adjacent blood vessels also need to be considered to better complete the procedure, and this is especially true for microsurgical clipping. Clarifying the anatomy before surgery is helpful for better selecting the surgical approach and surgical side, which could affect the intraoperative exposure of the aneurysm and adjacent arteries, the surgical difficulty, the resection rate and the postoperative complications. Therefore, starting with Anterior communicating artery aneurysms and their adjacent structures and variations, this paper reviews the latest progress in surgical treatment based on anatomic specificity as well as the most recent clinical studies.